Employers Opting Out of Public Disability Insurance: Selection or Incentive Effects? - Wolter H.J. Hassink; Pierre Koning; Wim Zwinkels (Tinbergen Institute, 2015)
This paper analyzes selection and incentive effects of opting out from public to private insurance on employer Disability Insurance (DI) inflow rates. We use administrative information on DI benefit costs and opting-out decisions of a balanced panel of about 140,000 employers that are observed between 2007 and 2011. We argue that the opting-out decision of employers was driven by current DI enrolment and anticipation effects that resulted from short-term expectations on DI costs. In particular, employers opted out when this was most rewarding for them in reducing DI premium rates. When controlling for these effects, our main finding is that there are no incentive effects due to opting out. Thus, publicly and privately insured employers show similar DI inflow rates.
Keywords: C23; I13; 330; Public versus private insurance; Disability insurance; Opting out; Longitudinal analyses